Epidemiology of Drug-resistant Tuberculosis in a Tertiary Care Center in Oman, 2006−2015 - Zied Gaifer; Ahmed Babiker; Dawar Rizavi (Oman Medical Journal, 2017)
Objectives: The aim of this study was to estimate the prevalence and identify the risk factors for the development of drug-resistant Mycobacterium tuberculosis infection in a tertiary care center in Oman. Methods: We performed a cross-sectional review of culture-confirmed tuberculosis (TB) cases diagnosed at Sultan Qaboos University Hospital between August 2006 and March 2015. We compared drug-resistant TB cases with drug-sensitive cases to identify predictors of drug-resistant TB using univariate and multivariate logistic regression analysis. Results: Of the 260 TB cases reviewed, 73.1% were confirmed by culture. The proportion of multi-drug resistant TB was 1.8%. TB isolates resistant to any of the first-line TB drugs comprised (7.5%) of cases. Pyrazinamide monoresistance was the most frequently reported drug monoresistant pattern (3.5%). Previous treatment for TB (odds ratio (OR) 14.81; 95% CI 3.09−70.98, p < 0.001), female gender (OR 3.85; 95% Cl 1.07−13.90, p < 0.039), and younger age (OR 6.80; 95% Cl 1.61−28.75, p < 0.009) were found to be risk factors for development of first-line antituberculosis drug-resistant TB in multivariate analysis. Conclusions: Our results show that the rate of drug-resistant TB in our population is a public health issue of great concern. Previous treatment with antituberculosis drugs, female gender, and younger age are risk factors for the development of drug-resistant TB. These findings are useful adjuvants to guide clinicians and public health professionals in the early detection and appropriate treatment of cases of drug-resistant TB.